An empirical study on the effectiveness of the Bachelor in Information Technology (BIT) curriculum of Universiti Utara Malaysia: From the industry perspective - C. Valida, Abelardo; Hashim, S.; Md Dahalin, Zulkhairi (Universiti Utara Malaysia, 1994)
This paper presents an initial assessment of the effectiveness of UUM's Bachelor in Information Technology curriculum using empirical data from the industry. The industry supervisor's rating of BIT practicum students for the School Year 1993-94, representing the first batch of graduates of this program, was used as the main data for the study. This "macro model" approach attempts to gauge the curricular study program including the learning environment of students by meaning such factors as (1) values and work ethics, (2) analytical abilities, and (3) leadership and communication capabilities and potentials. A total of 67 subjects working with 41 industries in Peninsular Malaysia, was used in the study. Another survey aimed at assessing the students' prepared for the practicum training was likewise conducted. Findings reveal that the curriculum under investigation is able to instill and nature essential characters along the recognized domains of education. A very interesting outcome, as a whole, is that the study program is very responsive from the technological-managerial considerations. Its ingredients turns out to be generally complete and up to date. Improvements are, however, suggested in terms of communications and analytical abilities.